A ideologia dos meios de comunicação social na formação da consciência familiar - Chaman, Terezinha de Jesus Bellote [UNESP] (2014)
A new communicational ideology gives us a real idea our present time. It is necessary to discuss, carefully, the sources of information and the cultural domain of communication. This present thesis, Ideology of the television media in the formation of the familiar consciousness, tries to discuss a vital questioning for the 20th century man: how electronic mass media (television) builds its discourses and how it contributes to the formation of the individual and family consciousness. The idea is to know how this communication discourse, that is due to be put away in the permanent movement of the social dynamics, builds its roots, modeling everyday life, building history, creating types, habits, attitudes… It can go straight to the media criticism, starting from Horkheimer/Adorno (1985) up to Machado (2000) without leaving aside Habermas (1981, 1984 e 1989), Bourdieu (1997), Baudrillard (1997) e Lipovetsky (2004). The objective is to show the need for a conception of the world and of ourselves, facing the other, a strong image so well drawn from Marx, Capital (1971). It favors the approach of the dialectic and hypothetic-deductive method which supports a qualitative research. The semi-structured interview is the first necessary instrument to collect the data and questions the television midia documentation that emphasizes the family as a theme. On the other hand, the critical reading is the essential practice so that the spectator can be transformed into a history builder of everyday life history and, at the same time, a subject of this same history. Those are the fundamental conditions for the formation of a critical citizen. The world challenge nowadays is to determine which role the family will play as the builder of people, if the goal is to have a just, solidary and ethic society. This text is part of the interdisciplinary Post-Graduation Program in Social Service, School of Social and Human...